Respect for elders as a tradition of upbringing in a modern Khakass family - Klavdiya I. Sultanbaeva (Publishing house "Sreda", 2023)
The article discusses the results of an empirical study of the tradition of raising respect for elders in children of six or seven years old in a modern Khakass family. The relevance of the study is due to the need to familiarize the younger generations with the traditional values of the people and the formation of the spiritual and moral culture of the child's personality. The purpose of the study is to study the traditions of upbringing in the Khakass family, namely, a respectful attitude towards elders. One of the tasks of the work was the study of the moral ideas of children of senior preschool age. The study was conducted in the kindergarten "Kalinka" in Abakan on the basis of empirical methods and the research methodology "Subject Pictures". The modern Khakass family is influenced by transformational processes and partially preserves ethno-cultural traditions. The tradition of respect for elders and adults is recognized by respondents as significant in the moral education of children, but is not considered as an independent cultural value. In the modern Khakass family, the described tradition in the moral education of children is partially preserved. In the moral ideas of older preschoolers, holistic reasoning about good and bad, good and evil prevails, there is an idea of helping elders, but the understanding of the concept of "respect for elders" is still poorly formed.